Clostridium difficile infection in fever patients with gynecological malignancies. Issue 5 (22nd July 2019) - Yanazume, Shintaro; Tokudome, Akio; Fukuda, Mika; Togami, Shinichi; Kamio, Masaki; Ota, Shunichiro; Kobayashi, Hiroaki
Abstract: Background: Although Clostridium difficile infection (CDI) often results in severe manifestations due to toxin‐producing clostridium, the correlation between CDI and having a fever in gynecological malignancies is not completely understood. Aims: The incidence, and clinical features, and clinical management of CDI in patients with gynecological malignancies who have fevers were investigated, and the clinical managements of this complication are discussed. Methods and results: We retrospectively reviewed 485 patients newly diagnosed with invasive gynecological cancers who underwent anticancer treatment between July 2012 and December 2016. The diagnosis of CDI was performed using enzyme immunoassays for C difficile glutamate dehydrogenase and toxin A/B enzyme immunoassay. The cumulative risk of CDI was 9.5% (six of 63) in overall fever patients and 6.3% (six of 95) in patients with fever episodes. Two CDI patients (33.3%) did not show diarrheal symptoms, with the fever of unknown origin criteria prompting their CDI testing and diagnosis. CDI patients were treated using vancomycin or metronidazole without suffering from fatal clinical course. Overall, eight patients with gynecological malignancies were diagnosed with CDI, including two patients with fever lower than 38.5°C. The cumulative risk of CDI was 0.48% (eight of 1652) for all admitted patients and 1.6% (eight of 485) in those with gynecological malignancies. Of all the patients with confirmed CDI, only one had a history of administration of antibiotics prior to onset of CDI symptoms. Conclusion: CDI does not always present with typical manifestations in malignancy patients. Investigation of CDI, regardless of gastrointestinal symptoms or history of antibiotic use, is warranted in cases of fever of unknown origin in gynecological malignancy.